Workshop for qualifying preceptors in Family and Community Medicine: a qualification strategy in Family and Community Medicine and Primary Care - Fernandes, Carmen Luiza Correa (2007)
The authors were designated by the Brazilian Society of Family Medicine and Community (SBMFC) to develop a workshop to train preceptores this speciality. The training aimed to guide the training of doctors from national guidelines because of the opening of new programs in Medical Residency in Family and Community Medicine at (PRMMFC) and the adequacy of existing ones. The task has been fulfilled, multiplication started and suffered evaluation.We want to share this experience through this article with others who have an interest in forming resources to qualify the health care in our country.